2020
DOI: 10.1051/0004-6361/201935866
|View full text |Cite
|
Sign up to set email alerts
|

Cloud formation in the atomic and molecular phase: H I self absorption (HISA) towards a giant molecular filament

Abstract: Molecular clouds form from the atomic phase of the interstellar medium. However, characterizing the transition between the atomic and the molecular interstellar medium (ISM) is a difficult observational task. Here we address cloud formation processes by combining H i self absorption (HISA) with molecular line data. Column density probability density functions (N-PDFs) are a common tool to examine molecular clouds. One scenario proposed by numerical simulations is that the N-PDF evolves from a log-normal shape … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 128 publications
(184 reference statements)
7
71
1
Order By: Relevance
“…Riener et al (2020) estimated the 13 CO(1-0) optical depth for GMF24, and found a median τ value of ∼0.5. Wang et al (2020) found that the GRS 13 CO(1-0) optical depth for another filament, GMF38a (l ∼ 33 • −37 • ), is mostly smaller than 1 with a median value of ∼0.4. If we apply this 0.4 to GMF54, the column density increases by ∼21%.…”
Section: Uncertaintiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Riener et al (2020) estimated the 13 CO(1-0) optical depth for GMF24, and found a median τ value of ∼0.5. Wang et al (2020) found that the GRS 13 CO(1-0) optical depth for another filament, GMF38a (l ∼ 33 • −37 • ), is mostly smaller than 1 with a median value of ∼0.4. If we apply this 0.4 to GMF54, the column density increases by ∼21%.…”
Section: Uncertaintiesmentioning
confidence: 91%
“…The 13 CO N-PDF can be better described with a log-normal function, but we still could not recover the log-normal peak of the N-PDFs. Wang et al (2020) studied the N-PDFs of the atomic and molecular gas in the giant molecular filament GMF38a, and found that the N-PDF of H I emission has the smallest width, followed by the cold neutral media traced by H I self absorption (HISA), and the 13 CO N-PDF has the largest width. It seems that the width of the N-PDF is correlated with the density it traces.…”
Section: N-pdfs Of the Whole Filamentmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 CO emission peaks at different velocities are not associated with GMF20.0-17.9 as their velocities are attributed to neighboring spiral arm structures (e.g., Vallée 2008;Reid et al 2014Reid et al , 2019. For the analysis of the physical properties of HISA, we followed the derivation by Gibson et al (2000) and Wang et al (2020a). A comprehensive discussion of the radiative transfer of HISA clouds is given in Gibson et al (2000), Kavars et al (2003), and Li & Goldsmith (2003).…”
Section: H I Self-absorption (Hisa) Extractionmentioning
confidence: 99%
“…Observations of H I 21cm line A68, page 1 of 21 A&A 642, A68 (2020) emission are generally attributed to both warm neutral medium (WNM) and CNM. To separate the WNM from the CNM, we make use of the presence of H I self-absorption (HISA; see e.g., Riegel & Crutcher 1972;Knapp 1974;van der Werf et al 1988;Feldt 1993;Gibson et al 2000Gibson et al , 2005aKavars et al 2003;Dénes et al 2018;Wang et al 2020a) to trace the cold atomic phase. H I self-absorption is found throughout the Milky Way in various environments.…”
Section: Introductionmentioning
confidence: 99%